Development of Screening Model for Psidium Guajava Cultivars for their Nutritive Potential - Verma, Uma (TIET, Patiala, 2019)
In the present study the two guava cultivars Shweta & Allahabad safeda were studied for their (Total phenolic content) TPC & (Total flavonoid content) TFC as they have direct correlation with the antioxidant activity and due to the metal chelation property of flavonoids, metal flavonoids complex have more potential to show the antioxidant activity. The maximum TPC (13.58±0.02) TFC (6.51±0.02) was found in the acetone extract of Shweta guava cultivar than the acetone extract of Allahabad safeda, TPC (10.22±0.14) and TFC (6.33±0.04) and the methanol extract of both the cultivar showed the minimum phenolic and flavonoid content. The maximum antioxidant activity in acetone extract of Shweta guava cultivar (94.50%), acetone extract of Allahabad safeda guava cultivar (92%) than the methanol extract of both the guava cultivars. All the above maximum results were obtained at 40 minutes of the treatment time by using the probe tip ultrasonication (20 kHz, 100W) extraction method. Whereas, comparatively low results were found with the bath ultrasonication (33 kHz, 100W) extraction technique used for 40 minutes of treatment time for both the guava cultivars. For the identification of possible flavonoids present in guava cultivars, TLC was performed by using mobile phase (Toluene: ethyl acetate: formic acid) (5:4:0.2). After the identification of possible flavonoids the HPLC analysis of each extract prepared was done against the standard quercetin by using solvent system (acetonitrile: methanol: water) (15:40:45) In which the maximum amount of quercetin was detected in acetone extract of Allahabad safeda guava cultivar (103.515µg/ml) and Shweta guava cultivar (101.047µg/ml) and minimum amount of quercetin was detected in methanol extract of both the cultivars. The characteristic property of complexation of flavonoids with metals were studied with the analytical model proposed by using the MEMS technology which showed that when the mass of the quercetin metal complex added on the microcantilever beam, the tip displacement(µm) was observed with respect to time (µs) against the standard quercetin and hence change in capacitance between the movable and fixed electrode of microcantilever beam was observed.
M. Sc. Biotechnology thesis
Keywords: Flavonoids; Metal flavonoids complexation; MEMS; Open loop control technique; Capacitance